Disparities in Acute Pain Treatment by Cognitive Status in Older Adults With Hip Fracture. (27th September 2019) - Chang, Andrew K; Edwards, Robert R; Morrison, R Sean; Argoff, Charles; Ata, Ashar; Holt, Christian; Bijur, Polly E
Abstract: Background: We examined the disparities in emergency department (ED) pain treatment based on cognitive status in older adults with an acute hip fracture. Methods: Observational study in an academic ED in the Bronx, New York. One hundred forty-four adults aged 65 years and older with acute hip fracture were administered the Telephone Interview for Cognitive Status (TICS) while in the ED. The primary outcome was receipt of any parenteral analgesic. The risk factor of interest was cognitive impairment (TICS ≤ 25). Secondary outcomes included receipt of any opioid, receipt of any analgesic, total dose of analgesics in intravenous morphine equivalent units (MEQ), and time to receiving first analgesic. Results: Of the 87 (60%) study patients who were cognitively impaired, 60% received a parenteral analgesic compared to 79% of the 57 cognitively unimpaired patients (RR 0.76 [95% CI 0.61, 0.94]). The effect of cognitive impairment on receiving any opioids (RR: 0.81, 95% CI 0.67, 0.98) and any analgesic (RR: 0.85; 95% CI: 0.71, 1.01) was similar. The median analgesic dose in cognitively impaired patients was significantly lower than in cognitively unimpaired patients (4 MEQ vs 8 MEQ, p = .003). Conclusion: Among older adults presenting to the ED with acute hip fracture, cognitive impairment was independently associated with lower likelihood of receiving analgesia and lower amount of opioid analgesia.